Ion irradiation and reduction effect on the conductivity of heavily MgO + Fe2O3-doped LiNbO3 single crystals; Korus 2004; Vol. 2 - Pichugin V. F. Vladimir Fyodorovich; Bulycheva A. A.; Yakovlev V. Yu. Viktor Yurjevich; Ill Won Kim (2004, 2004)
The effect of the insulator-conductor transition of surface layers of oxides by ion bombardment was investigated by the example of doped LiNbO3 single crystals. The important role of reduction in modification of conducting properties of the ion-irradiated crystals was established. The action of reduction on the electric characteristics of crystals LiNbO3 is similar to that of ion bombardment A new band of optical absorption with a maximum at 3.7 eV caused by presence of Mg impurity in LiNbO3+ MgO was founded. The comparative analysis of electric properties of reduced and irradiated by Ar+ ions crystals shows, that conductivity of the lithium niobate ion-modified layers is carried out by polarons hopping.